Agricultural liming contributes to global warming - Dumale, Wilfredo A. Jr.; Hirai, Kenta; Nishimura, Taku; Miyazaki, Tsuyoshi; Imoto, Hiromi (2011)
The role of atmospheric CO2 in global warming is unchallenged. Lime carbonates contribute to atmospheric CO2 emissions and enhance soil organic carbon (SOC) turnover in limed acid soils. Experimental data on the magnitude of lime-contributed CO2 are still few although liming is common agricultural practice worldwide. To separate lime-contributed and SOC-originated CO2-C to CO2 evolution, we used CA13CO3 (13C 99%) as lime and tracer to an acidic Kuroboku Andisols from Tanashi, Tokyo Prefecture (35ᵒ44’N, 139ᵒ32’E) and Kunigami Mahji Ultisols of Nakijin, Okinawa Prefecture, Japan (26ᵒ38’ N, 127ᵒ58’ E). The lime was applied under two soil water conditions: 70% (FC70) and 30% (FC30) of the field capacity (FC) of the soils incubated at constant temperature (20ᵒC). After 36 days, 13CO2-C ecolutions was 74.37 – 79.32% of total CO2-C emissions from Kuroboku Andisols, and 62.32 – 70.4% in Kunigami Mahji Ultisols. This confirmed significant contribution of carbonates in CO2 evolution of limed agricultural soils. Liming also increased 12CO2-C evolution from native SOC. Priming effect of lime ranged from 51.97 – 114.95% in Kuroboku Andisols and 10.13 – 35.61% in Kunigami Mahji Ultisols. These are real priming effects since there was no other source of 12CO2-C than SOC. Decreasing in soil microbial biomass carbon (SMBC) indicated microbial stress due to liming, and rise in soil pH allowed in microbial populations able to utilize SOC, explaining the extra 12CO2-C evolution in lime soils.
Keywords: Soil organic carbon; Soil salinity; Global warming; Carbon dioxide